Mixed culture of bangos, sugpo/alimango and salt making a report on the practice in industry in fish culture - Manalo-Manalo, Nonila A. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1973)
Far reaching changes have been occurring in the economy of the Philippines in the last decade. For one thing this is the age of better fisheries in the Philippines. Diversification, mergers and innovations mark this era in Philippines fisheries. Never has competition been so keen, the market so demanding, population so explosive and technology so advanced. It is the age of the new society and as people shout for "change", change for the better we must. In keeping up with this age, this report designs to provoke change in fisheries students. The traditional descriptive approach to basic organization and fisheries courses had lulled the fisheries students as a major course. This reports still some traditional principles of fisheries even as included, for these two cannot part ways so easily. It is the author's hope that the report will provide the young students with the vision and proper orientation as to what better fisheries is. To those who are already in the front line of fisheries, it is hoped that this may provide a quick refresher and a new perspective in fish culture.
Submitted to the College of Fisheries, University of the Philippines in partial fulfillment of the requirements for graduation in fish culture 1973.
Keywords: Fish-culture.